The Role of Transformational Leadership in enhancing Engagement and Motivation of Millennial Employees - Bahiroh, Eloh; Ikhlas, Ramadhani (Penelitian dan Pengembangan Ilmu, 2024)
Transformational leadership has become a key approach in increasing the engagement and motivation of millennial employees, who are an important segment of today's workforce. This research aims to explore how transformational leadership can be optimized with the help of digital technology to increase the involvement and motivation of millennial employees. The method used is a systematic literature review using the PRISMA approach, including articles from reputable international databases. The research results show that transformational leadership, supported by digital technology, can strengthen the engagement and motivation of millennial employees through increasing efficiency, communication and career development opportunities. The implications of these findings suggest that organizations adopt transformational leadership and utilize digital technology to create more productive and adaptive work environments.